2018
DOI: 10.12998/wjcc.v6.i15.936
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on operative trauma between microwave ablation and surgical treatment for papillary thyroid microcarcinoma

Abstract: AIM To compare the effect and postoperative trauma of ultrasound-guided percutaneous microwave ablation and surgical resection in the treatment of papillary thyroid microcarcinoma (PTMC). METHODS Eighty-seven patients with PTMC treated at Fudan University affiliated Shanghai Fifth People’s Hospital were enrolled as subjects. The patients were divided into a microwave ablation group (41 cases) and a surgical group (46 cases). The operative time, intraoperative blood loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…In our LA group, hypocalcemia did not occur, and, to the best of our knowledge, it has not been reported in the PTMC cases treated by RFA and MWA [11,12]. However, transient hoarseness has been reported after MWA and RFA [12,33]. It did not develop in our LA group.…”
Section: Discussionsupporting
confidence: 39%
“…In our LA group, hypocalcemia did not occur, and, to the best of our knowledge, it has not been reported in the PTMC cases treated by RFA and MWA [11,12]. However, transient hoarseness has been reported after MWA and RFA [12,33]. It did not develop in our LA group.…”
Section: Discussionsupporting
confidence: 39%
“…The MWA group had similar preoperative ALT and AST levels but lower immediately postoperative ALT levels compared with the SR group. A large amount of evidence supports the concept that the risk of LTP and OS after MWA or SR are driven by unmodifiable patient-and tumor-related factors [23][24][25][26][27]. The size and number of LM lesions may increase the difficulty of operation and fail to enlarge the safety margin, resulting in poor tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no residue was identified among six MWA studies. Three articles investigated MWA procedure comparing with surgery and reported that MWA, as a minimally invasive treatment of PTMC, embraced lower incidence rate of complications and without decreasing the therapeutic effect 6, 42, 45. The hospital stay, surgery/procedure time is significantly shorter in MWA group than surgery group (Table 5).…”
Section: Us-guided Microwave Ablation (Mwa)mentioning
confidence: 99%
“…Considering the indolent feature of PTMC, treatments' efficacy, safety and even medical economy should be taken into consideration. As to surgical procedure, high patients' costs and long hospital stay were unavoidable and, in some case, patients' post-operative life quality will be even worse than pre-operation if related complication happens 6. As to AS, some patients' progressing anxiety and heavily psychological burden, because of the tumor diagnosis and the probability of progression, could lead to decreasing life quality even if doctor had interpreted the benign-like feature of this disease.…”
Section: Introductionmentioning
confidence: 99%